Non-contiguous finished genome sequence and description of Kurthia massiliensis sp. nov. - Roux, Véronique (Michigan State University, 2012)
Kurthia massiliensis strain JC30(T) sp. nov. is the type strain of K. massiliensis sp. nov., a new species within the genus Kurthia. This strain, whose genome is described here, was isolated from the fecal flora of a healthy patient. K. massiliensis is a Gram-positive aerobic rod. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 3,199,090 bp long genome contains 3,240 protein-coding genes and 86 RNA genes, including between 3 and 4 rRNA genes.